Identification of hazards and critical control point (CCP) for cassava fufu processing in South West Nigeria - Obadina, A.O.; Oyewole, O.B.; Sanni, Lateef O.; Tomlins, Keith I.; Westby, Andrew (Elsevier, 2008)
A hazard analysis survey of wet fufu processing was carried out for Wve processors around Abeokuta. This analysis consisted of observing the raw materials and environment, watching all steps of the processing, recording pH during steeping/fermentation, and collecting of samples from diced cassava, washed cassava, soaked cassava and wet fufu for total viable count, Coliform, Staphylococcal and Bacillus counts. The pH of steeping/fermentation for the processors varies between 4.08 and 4.58. The total viable count increases with increase in pH level of the wet fufu and Coliforms, Bacillus cereus and Staphylococcus aureus were isolated from the wet fufu. The presence of Coliforms, S. aureus and B. cereus indicates that the processing is carried out in a highly contaminated environment. Education of processors on the hazards, critical control point (CCP) and the importance of hygienic environment is imperative. Therefore, control measures and proper monitoring procedures for wet fufu processing are suggested.